1997
DOI: 10.2307/2953416
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Adolescents' Risk For Late Entry into Prenatal Care

Abstract: Risk factors for late entry into prenatal care were examined among 533 pregnant adolescents younger than 18. Forty-seven percent entered prenatal care after 12 weeks' gestation. Logistic regression analysis indicated that adolescents who no longer had contact with their baby's father were 4.2 times as likely as those who did to enter prenatal care after the first trimester. Adolescents with no history of abortion were 3.2 times as likely to enter care late as those who had had an abortion. Young women who had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 11 publications
1
16
0
6
Order By: Relevance
“…[1][2][3][4] Causes for the poorer birth outcomes in adolescents have been ascribed to lower rates of adequate prenatal care, 5 poor weight gain and nutrition, 6 higher rates of tobacco use, high-risk health behaviors, 7 and socioeconomic background characteristics. 8 For the most part, teen pregnancy and childbearing studies refer to 15-19-year-old mothers and do not often include childbearing in adolescents ,15 years old.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Causes for the poorer birth outcomes in adolescents have been ascribed to lower rates of adequate prenatal care, 5 poor weight gain and nutrition, 6 higher rates of tobacco use, high-risk health behaviors, 7 and socioeconomic background characteristics. 8 For the most part, teen pregnancy and childbearing studies refer to 15-19-year-old mothers and do not often include childbearing in adolescents ,15 years old.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The timing of prenatal care initiation can be influenced by numerous prepregnancy factors, including maternal educational attainment, [1][2][3][4][5][6] age, [1][2][3][4][5][6][7][8] parity, 2,6,7 ethnicity, 3 women's feeling about pregnancy and prenatal care, 6 and insurance. 2,[8][9][10][11] In the last two decades, some investigators have demonstrated the importance of preconceptional care to improve perinatal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, being younger than 18 years old is often used as a criterion for enrollment into PCM, as is required for Nurse-Family Partnership PCM [21][22][23][24]. Several studies indicate that adolescent mothers do not obtain prenatal services or tend to delay initiation of prenatal care [18,19,25]. Despite the known health risks related to adolescent pregnancy [26], the overall breadth of problems experienced by pregnant adolescents nationally remains unclear due to the limited attention given to differences in their underlying social, economic, psychological, or other risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents are particularly at risk during pregnancy, as this time period is often associated with inadequate prenatal care and poor birth outcomes, notably low birthweight and premature birth [18][19][20]. For this reason, being younger than 18 years old is often used as a criterion for enrollment into PCM, as is required for Nurse-Family Partnership PCM [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%